2019
DOI: 10.1186/s12870-019-1975-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and genomic organization analyses of chloroplast DNA invasions in the nuclear genome of Asparagus officinalis L. provides signatures of evolutionary complexity and informativity in sex chromosome evolution

Abstract: Background The transfer of chloroplast DNA into nuclear genome is a common process in plants. These transfers form nuclear integrants of plastid DNAs (NUPTs), which are thought to be driving forces in genome evolution, including sex chromosome evolution. In this study, NUPTs in the genome of a dioecious plant Asparagus officinalis L. were systematically analyzed, in order to investigate the characteristics of NUPTs in the nuclear genome and the relationship between NUPTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 51 publications
(69 reference statements)
1
20
1
Order By: Relevance
“…NUPTs and NUMTs are frequently organized as clusters [21,38,39]. For example, we observed that approximately 45% of the 3155 NUPT insertions were organized in clusters in the genome of Asparagus officinalis [21].…”
Section: Organization and Distribution Patternsmentioning
confidence: 85%
See 4 more Smart Citations
“…NUPTs and NUMTs are frequently organized as clusters [21,38,39]. For example, we observed that approximately 45% of the 3155 NUPT insertions were organized in clusters in the genome of Asparagus officinalis [21].…”
Section: Organization and Distribution Patternsmentioning
confidence: 85%
“…NUPTs and NUMTs are frequently organized as clusters [21,38,39]. For example, we observed that approximately 45% of the 3155 NUPT insertions were organized in clusters in the genome of Asparagus officinalis [21]. In the model plant species Arabidopsis and rice, NUPTs and NUMTs are frequently nonrandomly arranged as loose clusters or tight clusters based on the physically linked degrees [39].…”
Section: Organization and Distribution Patternsmentioning
confidence: 90%
See 3 more Smart Citations